Characteristics and predictors of allergic rhinitis undertreatment in primary care. (March 2016) - Spinozzi, F; Murgia, N; Baldacci, S; Maio, S; Pala, AP; Casciari, C; dell'Omo, M; Viegi, G; ,
Although allergic rhinitis is considered a raising medical problem in many countries it is often undertreated. The reasons for this phenomenon are not completely clear. The aim of this study is to evaluate factors associated with allergic rhinitis under-/no treatment. A sample of 518 allergic rhinitis patients recruited by their primary care physicians, as a part of the ARGA study, were invited to fill in a specific questionnaire regarding rhinitis symptoms, treatment, and rhinitis-related work/social disability. Chi-square test and logistic regression were performed to assess risk factors for allergic rhinitis under-/no treatment. Over one out of four patients had no treatment despite the symptoms and 13.5% were inadequately treated. Participants with asthma (OR 0.47, 95% CI 0.30–0.75) and conjunctivitis (0.44, 95% CI 0.27–0.71) were at lower risk of allergic rhinitis under-/no treatment: in asthmatics this reduction was related mainly to the concomitant asthma treatment (OR 0.19, 95% CI 0.10–0.37). Asthmatics with under-/not treated rhinitis had the highest prevalence of rhinitis-related quality of life impairment. Under-/no treatment for allergic rhinitis is still rather frequent despite the relevance of this disease. The simultaneous presence of asthma and an anti-asthmatic therapy are able to influence positively the treatment. Targeted interventions toward a better characterization and a tight follow-up of rhinitis patient without asthma are needed.